(untitled) (Singapore, 1998)
The objectives of this study are: *) Some economic activities, namely, collection of wood and minor forest products, and capture fisheries in mangrove area. **) Environmental and ecological services such as the export of biomass and service as a nursery ground for the marin life essential for off-shore fisheries. Other functions include carbon sequestration, storm protection, shore stabilization, and the control of soil erosion and flooding. These values are foregone benefits of mangroves which should be compared with the net returms from full conversion of mangrove areas into commercially intensive shrimp farms.
Keywords: economic development projects